Comparative Study of Lean Practices between Japanese and Malaysia Automotive Service Centres: A Survey Result - Ahmad, Md Fauzi; Ting, Neo Yeong; Muhd Nor, Nik Hisyamudin; Shiaw Wei, Chan; Hassan, Mohd Fahrul; Abdul Hamid, Nor Aziati (International Journal of Supply Chain Management, 2017)
Lean practices is not only a business philosophy but also a management tool which has recognised highly benefits to decrease costs, remove waste, increase productivity and improve quality and profit. Nowadays, lean practices are implemented in many manufacturing and services companies. Lean practices are implemented in order to minimize wastes while maximise the overall performances in an organisation. In service sector, lean practices are importance to ensure value added services can be delivered to customers. However, Malaysia automotive companies cannot compete with Japanese automotive companies in terms of their customer satisfaction. The purpose of this study is to compare the lean practice between Japanese and Malaysia automotive service centres. A total of 80 questionnaires out of 100 distributed questionnaires were responded and this represented as 80% of response rate. The Mann-Whitney test result shows that there were four out of five factors of lean practices have significant differences between Japanese and Malaysia automotive service centres, which are TPM, JIT, Kanban, and 5S. VSM has not significant difference between ownerships. In addition, TPM, JIT, Kanban, VSM and 5S were higher practices in Japanese companies against Malaysia companies. Many Malaysia companies are still in the journey of lean practices and they need recommendation guidance to compete with other long-term established companies. Based on the survey result, the significant differences are identified as weak points of Malaysia companies as an opportunity to improve. Moreover, the significance of this study can help researchers and industry players to improve lean practices in automotive service industry.